2014
DOI: 10.1039/c4an01086h
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric and fluorescent determination of sulfide and sulfite with kinetic discrimination

Abstract: General rights It is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 37 publications
0
15
0
2
Order By: Relevance
“…In our previous work, we found that the nucleophilic reactivity 183 decreases in the order: sulfite > sulfide > thiol [26]. The results in 184 Fig.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…In our previous work, we found that the nucleophilic reactivity 183 decreases in the order: sulfite > sulfide > thiol [26]. The results in 184 Fig.…”
mentioning
confidence: 57%
“…In our previous work, 20 we designed several probes for sulfur-containing compounds by 21 incorporating a,b-unsaturated ketone on a coumarin fluorophore 22 [26][27][28]. The experimental results revealed that a strong electron- 23 donating group suppressed the Michael reaction.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Bottom: representative fluorescence images of mice (pseudocolour) that were injected with 68-Cu(II) (40 mm), followed by Na 2 S. The images were recorded after the injection of Na 2 S within 5 h. Image reproduced with permission. 238 In order to keep this section to a reasonable length and highlight the most relevant recent examples it was not possible to include all recent examples of probes functioning by way of (i) nucleophilicity 100,218,219,223,224,[239][240][241][242][243][244][245][246][247] (ii) reduction (arylazides, [226][227][228][231][232][233][234][235][248][249][250][251][252][253][254][255][256][257][258] sulfonylazides, [259][260][261] nitro groups, 262,263 hydroxyl amines, 264 and N-oxides 265 ) as well as (iii) displacement 53,[266][267][268][269] and readers are referred...…”
Section: Hydrosulphidementioning
confidence: 99%
“…[3,4] Sulfites and bisulfites are often used as enzyme inhibitors and antiseptic agentsi nf ood, alcohol and pharmaceutical products because they can prevent oxidation and bacterial proliferation, as well as inhibit enzymatic and non-enzymatic browning. [5] Studies have shown that endogenous sulfur dioxide, which is produced from sulfur-containing amino acids, [6][7][8] plays as ignificant role in various physiological processes such as vasodilation,a ntioxidation and reduction of inflammation. [9,10] Although sulfur dioxide can be highly beneficial for the humanbody, an abnormal body level of sulfur dioxide can cause lung cancer, cardiovascular diseases and neurological disorders.…”
Section: Introductionmentioning
confidence: 99%